Towards a precision psychiatry approach to anxiety disorders with ecological momentary assessment: the example of panic disorder. Issue 1 (9th February 2020) - Robinaugh, Donald J; Brown, Mackenzie L; Losiewicz, Olivia M; Jones, Payton J; Marques, Luana; Baker, Amanda W
Abstract : Background: Treatments for anxiety disorders are among the most effective in psychiatry. Yet, there is considerable room for improvement. Aim: In this paper, we discuss the value of ecological momentary assessment as a research method and clinical tool. Methods: We begin by describing ecological momentary assessment and its advantages, including the ability to collect ecologically valid information about mental disorders, in real time, in individual patients. We then illustrate the value of this approach for anxiety disorder treatment using two patients with panic disorder who completed ecological momentary assessments for 2 weeks before and after a cognitive-behavioural therapy intervention. We focus especially on two key pieces of information provided by ecological momentary assessment data: information about symptom dynamics and information about the relationships among symptoms as they unfold over time within individual patients. Perspective: Although considerable work is needed to further develop this methodology in the context of anxiety disorder treatment, we believe that these pieces of information may ultimately inform our understanding of how anxiety disorder treatments have their effect and how those treatments can be tailored to individual patients.